CAR T Cells Redirected to CD44v6 Control Tumor Growth in Lung and Ovary Adenocarcinoma Bearing Mice - Porcellini, Simona; Asperti, Claudia; Corna, Stefano; Cicoria, Eleonora; Valtolina, Veronica; Stornaiuolo, Anna; Valentinis, Barbara; Bordignon, Claudio; Traversari, Catia (Frontiers in Immunology, 2020)
The main challenge of adoptive therapy with Chimeric Antigen Receptor modified T cells (CAR T) is the application to the field of solid tumors, where the identification of a proper antigen has emerged as one of the major drawbacks to CAR T cell treatment success. CD44 is a glycoprotein involved in cell-cell and cell-matrix interactions. The isoform containing the variant domain 6 of CD44 gene (CD44v6) has been implicated in tumorigenesis, tumor cell invasion and metastasis and represents an attractive target for CAR T cell therapies. Targeting CD44v6 antigen has been shown to control tumor growth in acute myeloid leukemia and multiple myeloma mouse models. While CAR T approach for the treatment of B cell malignancies has shown great success, response rates among patients with solid cancer are less favorable. The purpose of our study was to test the efficacy of CD44v6.CAR T cells, produced in compliance with Good Manufacturing Practice (GMP), in adenocarcinoma tumor models. We generated a bicistronic retroviral vector containing the CD44v6 CAR and the HSV-TK Mut2 suicide gene to enhance the safety of the proposed CAR T cell therapy. CD44v6 transduced CAR T cells were homogeneously positive for LNGFR selection marker, were enriched in T central memory (TCM) and T memory stem cells (TSCM) and displayed a highly activated phenotype. In vitro assays revealed antigen-specific activation and cytotoxicity of human CD44v6.CAR T cells against CD44v6 expressing tumor cell lines. When infused in immunodeficient tumor bearing mice, human CD44v6.CAR T cells were able to reach, infiltrate and proliferate at tumor sites, finally resulting in tumor growth control. Next, we checked if cells produced in compliance with GMP grade standards retained the same antitumor activity of those produced with research grade materials and protocols. Noteworthy, no differences in the potency of the CAR T obtained with the two manufacturing processes were observed. In conclusion, our preclinical results suggest that CD44v6.CAR T based adoptive therapy could be a promising strategy in solid cancer treatment.